Charge‐Transfer Effects of Organic Ligands on Energy Storage Performance of Oxide Nanoparticle‐Based Electrodes (Adv. Funct. Mater. 2/2022). (12th January 2022) - Song, Yongkwon; Lee, Seokmin; Ko, Yongmin; Huh, June; Kim, Yongju; Yeom, Bongjun; Moon, Jun Hyuk; Cho, Jinhan
Abstract : Charge Transfer Effects In article number 2106438, Jinhan Cho and co‐workers investigate the charge transfer effects of organic ligands depending on their size/functionality and interfacial interaction in the oxide nanoparticle‐based pseudocapacitor electrodes. The chemical reducing ligands with extremely small molecular size notably decrease the interparticle distance and simultaneously increase the number of oxygen vacancies in pseudocapacitive/conductive oxide nanoparticles, which can contribute to the formation of an efficient charge transfer pathway.